First record of Triatoma maculata (Erichson, 1848) (Hemiptera: Reduviidae: Triatomini) in Riohacha, La Guajira - Colombia - Edith Natalia Gómez-Melendro; Carolina eHernández; Catalina eGonzález-Uribe; Helena eBrochero (Frontiers Media S.A., 2014)
Introduction. Knowledge of vector insect species, their habitat and geographical distribution is crucial for determining the risk of transmission of the etiologic agents that cause disease in humans, which allows defining strategies for prevention, surveillance and control in line with the characteristics of each area. Objective. To determine the presence and public health importance of vectors of Chagas disease in the indigenous settlements of Marbacella and El Horno of the Wayúu ethnic group in the municipality of Riohacha, La Guajira, Colombia. Materials and methods. From active search, installation and inspection of biosensors and occasional catches, Hemiptera: Reduviidae: Triatomini were collected intra and in the peridomicile housing of the indigenous settlements of El Horno and Marbacella of the the Wayúu ethnic group. Indices of intra and peridomestic infestation, colonization, density, dispersion and natural infection with Trypanosoma cruzi Chagas, 1909 were calculated. Results. 79.6% (n = 90) of the specimens were collected around the homes and 20.3% (n = 23) inside the homes, all corresponding to Triatoma maculata (Erichson, 1848). The natural infection indices with T. cruzi accounted for 43.5% for Marbacella and 36% for El Horno. Conclusion. This is the first reported capture of individuals of T. maculata, considered a secondary vector of Chagas disease in Colombia, naturally infected with T. cruzi in the municipality of Riohacha expanding the geographical distribution of the species in the department of La Guajira.